2007
DOI: 10.1080/13576500701251981
|View full text |Cite
|
Sign up to set email alerts
|

Attention in musicians is more bilateral than in non-musicians

Abstract: Attention in neurologically intact adults normally errs towards the left side of space, as documented in studies involving tasks of visual attention (i.e., line bisection). The aim of this study was to further investigate lateralisation of attention in musicians and non-musicians. Reaction times and accuracy were recorded to stimuli presented to the left and right of a vertical line in 20 right-handed musicians and 20 matched non-musician controls. While both groups performed more accurately to left-sided stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 38 publications
6
41
1
4
Order By: Relevance
“…On the other hand, the heterogeneous range of musical instruments that we used suggests that the expertise effects measured in this study are unlikely to be based on the presence of specific local visual features, but rather indicate a more general and global level of perceptual expertise for musical instruments of various kinds. This suggestion is in line with previous findings that, relative to nonmusicians, musicians generally are faster and more accurate in tests of visual spatial perception and mental imagery (Brochard, Dufour, & Després, 2004;Patston, Hogg, & Tippett, 2007), have faster interhemispheric visual transfer times (Patston, Kirk, Rolfe, Corballis, & Tippett, 2007), and have larger cortical motor representations (Elbert, Pantev, Wienbruch, Rockstroh, & Taub, 1995). Note that these findings were not confined to the representations of musical instruments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, the heterogeneous range of musical instruments that we used suggests that the expertise effects measured in this study are unlikely to be based on the presence of specific local visual features, but rather indicate a more general and global level of perceptual expertise for musical instruments of various kinds. This suggestion is in line with previous findings that, relative to nonmusicians, musicians generally are faster and more accurate in tests of visual spatial perception and mental imagery (Brochard, Dufour, & Després, 2004;Patston, Hogg, & Tippett, 2007), have faster interhemispheric visual transfer times (Patston, Kirk, Rolfe, Corballis, & Tippett, 2007), and have larger cortical motor representations (Elbert, Pantev, Wienbruch, Rockstroh, & Taub, 1995). Note that these findings were not confined to the representations of musical instruments.…”
Section: Discussionsupporting
confidence: 80%
“…This difference in the extent to which congruency effects could be accounted for by an increased level of set size between the two subject groups was highly significant (z 3.61, p .001). In addition, the musicians showed larger congruency effects (M 48 msec) than did the nonmusicians (M 17 msec) [F(1,18) some of the tests in which the musicians showed performance advantages involved spatial-relational processing of visual stimuli (Brochard et al, 2004;Patston, Hogg, & Tippett, 2007). It is thus possible that the specificity of the advantage found in our study to the images of musical instruments, rather than to their names, reveals a more fundamental difference between the spatial and object recognition processing of visual 2-and 3-D objects as compared with verbal information (such as the letter strings in the name search task).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our earlier research showed that musicians bisected lines to the right of centre, and were also more accurate overall than non-musicians (Patston, Corballis, Hogg, & Tippett, 2006). In addition, when discriminating on which side of a vertical line a dot had been presented, musicians performed more equally to stimuli presented on both sides than did non-musicians, whose performance was significantly worse for dots appearing on the right side of the line (Patston, Hogg, & Tippett, 2007). These findings suggest that spatial attention is represented more bilaterally in musicians than in nonmusicians.…”
Section: E-mail Address: Lucypatston@gmailcom (Llm Patston)supporting
confidence: 47%
“…12 In another study it was stated that cognitive demand increase related to playing instruments with both hands could improve plasticity and visual attention. 13 This result made us think that long term music training improved data processing but not for attention. This might be related to the fact that musicians used auditory attention instead of visual attention in our study and they have better skills in this area.…”
Section: Discussionmentioning
confidence: 99%